2022
DOI: 10.3389/fimmu.2022.845064
|View full text |Cite
|
Sign up to set email alerts
|

RhoG’s Role in T Cell Activation and Function

Abstract: The role of RhoG in T cell development is redundant with other Racs subfamily members, and this redundancy may be attributed to redundant signal transduction pathways. However, the absence of RhoG increases TCR signalling and proliferation, implying that RhoG activity is critical during late T cell activation following antigen–receptor interaction. Moreover, RhoG is required to halt signal transduction and prevent hyper-activated T cells. Despite increase in TCR signalling, cell proliferation is inhibited, imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…With the exception of sCTLA-4, the number of correlated genes was sufficient for pathway analysis ( Figure 6B ). The enriched pathways for genes whose expression was positively correlated with sPD-L1 concentration included those related to cell proliferation and immune activation, whereas enriched pathways for genes correlated with sPD-1 level included those related to immune responses, T cell activation, and T cell anergy (signaling by Rho GTPases; Figure 6B ) ( 45 ). Examination of genes characteristic of naive, progenitor exhausted, or terminally exhausted T cells ( 46 ) revealed that the concentration of each soluble immune factor was highly correlated with the expression of genes associated with terminally exhausted T cells, but not with that of those associated with naive or progenitor exhausted phenotypes ( Figure 6C and Supplemental Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…With the exception of sCTLA-4, the number of correlated genes was sufficient for pathway analysis ( Figure 6B ). The enriched pathways for genes whose expression was positively correlated with sPD-L1 concentration included those related to cell proliferation and immune activation, whereas enriched pathways for genes correlated with sPD-1 level included those related to immune responses, T cell activation, and T cell anergy (signaling by Rho GTPases; Figure 6B ) ( 45 ). Examination of genes characteristic of naive, progenitor exhausted, or terminally exhausted T cells ( 46 ) revealed that the concentration of each soluble immune factor was highly correlated with the expression of genes associated with terminally exhausted T cells, but not with that of those associated with naive or progenitor exhausted phenotypes ( Figure 6C and Supplemental Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…ROGH is a member of the RHO family of small GTPases, playing a crucial role in regulating the equilibrium of T-cells.RhoG plays a part in the internalization of TCR at the immunological synapse (IS), a process crucial for effective T-cell activation. However, the current knowledge about this process is still insufficient 44 , CDK11A belongs to a group of protein kinases that encode serine/threonine proteins and are cleaved by cysteine asparaginase. It is suggested that CDK11A may be involved in the process of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Cdc42 deficiency results in the overactivation of murine T cells [ 98 ]. Moreover, RhoG and RhoH have been reported to regulate the TCR signaling pathway, mainly as the suppressor and enhancer, respectively [ 86 , 99 ].…”
Section: The Adaptive Immune Systemmentioning
confidence: 99%